Prof. H. Abdul Kahar Muzakkir and The Development of Islamic Reformist Movement in Indonesia - Mitsuo Nakamura (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2019)
This article discusses the life, struggle, and personality of Abdul Kahar Muzakki in 2019 was appointed as a National Hero. This study is based on the fact that information and studies on figures who play essential roles and contributions in the journey of the Indonesian nation are minimal. As a result, it is not uncommon for people to mistake and confuse him with another figure, Abdul Kahar Muzakkar, who is a DI/TII figure. Therefore, the article adapted from a scientific lecture was translated and presented again for today's audience. The first discussion focused on the early formative period of Abdul Kahar Muzakkir and his work in the world of education and national politics. Then, this article discusses Abdul Kahar Muzakkir's position and role in the dynamics of the Islamist movement and political exemplary at the local and national level. By seeing his example in attitude, religion, and politics, the writer can even refute the views of Harry J. Benda and Clifford Geertz who argued that Indonesian politics is based on contestation between priyayi, secular, and Islam (H.J. Benda) or exclusive politics (C.J. Geertz). Abdul Kahar Muzakkir's personality and political role show that politics is also a battle between authorities and ordinary folks where Islam acts as a source of inspiration and moral aspirations for people to realize a just and prosperous society.